2020
DOI: 10.3390/foods9010057
|View full text |Cite
|
Sign up to set email alerts
|

Management of Plant Physiology with Beneficial Bacteria to Improve Leaf Bioactive Profiles and Plant Adaptation under Saline Stress in Olea europea L.

Abstract: Global climate change has increased warming with a concomitant decrease in water availability and increased soil salinity, factors that compromise agronomic production. On the other hand, new agronomic developments using irrigation systems demand increasing amounts of water to achieve an increase in yields. Therefore, new challenges appear to improve plant fitness and yield, while limiting water supply for specific crops, particularly, olive trees. Plants have developed several innate mechanisms to overcome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Besides, in groundwater‐dependent arid ecosystems, plants could suffer from water stress when the groundwater depth is too deep, whereby soil water salinity could restrain plant growth when the water depth is too shallow (Maihemuti et al., 2021). Abiotic stress, such as water stress and salt stress, is one of the most deleterious environmental factors affecting plant growth, reproduction, and survivability during whole developmental stages (Galicia et al., 2020; Ma et al., 2020; Sun et al, 2010). Moreover, severe stress, including salt stress, may cease seed germination, decrease plant productivity (biomass) and growth status (vitality), and even lead to the death of the plants (Halik et al., 2019; Li, Si, Zhang, Gao, Luo, et al., 2019; Yu et al., 2018; Wang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in groundwater‐dependent arid ecosystems, plants could suffer from water stress when the groundwater depth is too deep, whereby soil water salinity could restrain plant growth when the water depth is too shallow (Maihemuti et al., 2021). Abiotic stress, such as water stress and salt stress, is one of the most deleterious environmental factors affecting plant growth, reproduction, and survivability during whole developmental stages (Galicia et al., 2020; Ma et al., 2020; Sun et al, 2010). Moreover, severe stress, including salt stress, may cease seed germination, decrease plant productivity (biomass) and growth status (vitality), and even lead to the death of the plants (Halik et al., 2019; Li, Si, Zhang, Gao, Luo, et al., 2019; Yu et al., 2018; Wang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these components have been demonstrated to be highly inducible. 10,12 Thus, citrus fruit peels could feasibly serve as rich and profitable sources for obtaining bioactive compounds highly valued in the food, health, pharmaceutical, and cosmetic fields, 1 where leveraging of citrus peels as a source of valuable products can contribute to a circular economy. Effective implementation of this proposal calls for efficacious, economical, and environmentally friendly techniques, such as the widely accepted use of BCAs or their derived molecules.…”
Section: Discussionmentioning
confidence: 99%
“…For example, olive leaves were demonstrated to exhibit significantly different levels of photosynthetic pigments, proline, soluble sugars, phenols, flavonols, and oleuropein following root inoculation by each of 10 beneficial bacteria. 12 Strawberry plants treated with Trichoderma spp. featured higher plant yield, growth, and productivity, as well as enhanced levels of anthocyanins in the corresponding fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The productivity of wheat is often unfavorably affected by salt stress, which has been linked to slow growth, changes in reproductive behavior, variations in enzymatic activity, damage to photosynthesis, injury to the ultrastructure of cell components, serotonin deficiency, and oxidative stress [10]. Many studies in the past have revealed the adverse effects of salt stress on the physiological traits of numerous plants, including cardoon genotypes [11], pepper [12], Vicia faba [13], and Olea europea L. [14]. Besides this, drought stress reduces morphological traits, such as leaf size and vegetative growth; physiological traits, such as reduction in photosynthesis and stomatal conductance; and the transpiration rate [15].…”
Section: Introductionmentioning
confidence: 99%